2008
DOI: 10.1007/s12311-008-0050-z
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-independent phospholipase A2 mediates store-operated calcium entry in rat cerebellar granule cells

Abstract: Store-operated Ca(2+) entry (SOCE) has been extensively studied in non-neuronal cells, such as glial cells and smooth muscle cells, in which Ca(2+)-independent phospholipase A(2) (iPLA(2)) has been shown to play a key role in the regulation of SOCE channels. In the present study, we have investigated the role of iPLA(2) for store-operated Ca(2+) entry in rat cerebellar granule neurons in acute brain slices using confocal Ca(2+) imaging. Depletion of Ca(2+) stores by cyclopiazonic acid (CPA) induced a Ca(2+) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 61 publications
3
16
0
Order By: Relevance
“…Singaravelu et al. [34] showed that phospholipase A2 mediates Ca 2+ influx in rat cerebellar granule cells.…”
Section: Discussionmentioning
confidence: 99%
“…Singaravelu et al. [34] showed that phospholipase A2 mediates Ca 2+ influx in rat cerebellar granule cells.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, recent evidence shows that PLA2 controls endothelial store‐operated Ca 2+ entry and vascular tone in intact aorta [Boittin et al, 2008], and enhances store‐operated Ca 2+ entry in dystrophic skeletal muscle fibers [Boittin et al, 2006]. Singaravelu et al [2008] showed that phospholipase A2 mediated store‐operated Ca 2+ entry in rat cerebellar granule cells. Thus, the present studies are consistent with data that phospholipase A2 activity was required for thimerosal‐evoked Ca 2+ signal in PC3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lupescu et al [2006] reported that human parvovirus B19 capsid protein VP1-evoked Ca 21 influx was inhibited if phospholipase A2 activity was suppressed. Evidence also shows that PLA2 regulates endothelial entry and vascular tone in intact aorta [Boittin et al, 2008], and stimulates store-operated Ca 21 entry in dystrophic skeletal muscle fibers [Boittin et al, 2006] and rat cerebellar granule cells [Singaravelu et al, 2008]. Another possible mechanism that might contribute to maprotiline-induced [ Lin et al, 2009;Lu et al, 2009].…”
Section: Discussionmentioning
confidence: 99%